AN EMPIRICAL ANALYSIS ON E- RETAIL SERVICE QUALITY, 3PL IN SUPPLY CHAIN L-SQUAL, E-SQUAL, AND E-SRQUAL - T C, Kavitha; Praharshith Rapoor, Pavan (International Journal of Supply Chain Management, 2019)
Electronic commerce brings huge business opportunities and revenue growth to companies like e- retailers, mainly due to its convenient, interactive, lower costs and high degree of customization and personalization to their customers. With respect to logistics outsourcing, online shopping takes place in the chain consisting of the third party logistics providers, e-retailer, and the customer, which represents a service triad. Since, the delivery service is provided by the third party logistics (3PL) service providers, the satisfaction level of the end customers depends on the combination of both product delivery service and e-retailers service. The study proposes a research model that integrates the e-service quality (ESQ), e- service recovery quality(ESRQ), and the logistic service quality(LSQ) that are provided by the e-retailers, which furthers influences both customer satisfaction and loyalty. The study examines the second order dimensions of ESQ, ESRQ, and LSQ using second stage reflective-formative approach. The outcome of the data analysis, with the sample size of 350, concludes that ESQ strongly influences LSQ, customer satisfaction (CS) and customer loyalty (CL) when using online retail websites. Similarly, when CS is achieved it also has a strong relationship on CL. The outcome of the analysis also evaluated that ESRQ has a strong influence on CS. The relationship between LSQ and CS, LSQ and CL are strongly significant, than ESQ and ESRQ Index Termsâ?? Service Quality, ESQ, ESRQ, 3PL and LSQ